(untitled) (LEARNing Landscapes, 2018)
Storytelling in the classroom has long been recognized for its many benefits, especially as a bridge from orality to literacy. With the changing demographic landscape present in current elementary classrooms across Canada and internationally, storytelling reaps additional benefits for promoting the goals of inclusion among diverse learner profiles. This article provides an updated literature review reflecting these shifting instructional mandates, offers practical ideas for using storytelling in the contemporary classroom, and provides an illustrative sample of a co-constructed story between student and teacher, highlighting the many ways in which storytelling benefits all learners.